CLINICAL EFFICACY AND SAFETY OF TRIPTANS VERSUS GEPANTS IN MIGRAINE MANAGEMENT: IMPLICATIONS FOR PHYSICAL ACTIVITY AND QUALITY OF LIFE - Magdalena Zięba; Szymon Rudawski; Maja Elertowicz (International Journal of Innovative Technologies in Social Science, 2026)
Introduction: Migraine is a chronic and disabling neurological disorder that substantially impairs daily functioning and limits participation in physical activity. Pharmacological management must therefore consider not only symptom relief but also safety, tolerability, and the ability to maintain functional and exercise capacity. Triptans have been the standard for acute migraine treatment, whereas calcitonin gene-related peptide (CGRP) receptor antagonists (gepants) have emerged as a newer therapeutic class without vasoconstrictive effects, potentially offering advantages for physically active individuals.Aim of the study: The aim of this article was to review and compare current evidence on the clinical efficacy, safety, cardiovascular considerations, and functional outcomes associated with triptans and gepants, with particular attention to implications for physically active individuals and sport participation.Methods and Materials: This narrative review was based exclusively on peer-reviewed full-text scientific articles provided by the author, including randomized controlled trials, long-term safety studies, meta-analyses, and mechanistic investigations related to triptans and CGRP receptor antagonists. Data were synthesized qualitatively with a focus on acute and preventive efficacy, adverse events, cardiovascular and exercise-related findings, and functional or quality-of-life outcomes.Conclusion: Triptans demonstrate superior acute efficacy in achieving pain freedom and pain relief; however, their vasoconstrictive properties, safety limitations, and low long-term adherence may restrict their suitability for some physically active individuals. Gepants provide clinically meaningful efficacy with a more favorable safety and tolerability profile, preserved exercise capacity, and improved functional outcomes, particularly in preventive treatment settings. These findings support gepants as a valuable therapeutic option for migraine management in patients for whom cardiovascular safety, exercise compatibility, and sustained functional performance are key considerations.